Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Kinerja Pegawai di PT. Garuda Indonesia Tbk - Setyorini, Albertha Dwi; Santi, Santi; Anggiani, Sarfilianty (E-Jurnal Akuntansi; Vol 31 No 2 (2021), 2021)
The purpose of this study was to analyze the influence of organizational culture and organizational commitment on employee performance at PT. Garuda Indonesia Tbk. The data used in this study are primary data with data collection methods, namely through questionnaires. The sample in this study were 60 employees at PT. Garuda Indonesia Tbk. The analysis technique in this research is through Multiple Linear Regression Analysis. The results of the analysis prove that organizational culture and organizational commitment simultaneously have a significant effect on employee performance at PT. Garuda Indonesia Tbk. Organizational culture and organizational commitment partially have a positive and significant effect on employee performance at PT. Garuda Indonesia Tbk Keywords: Organizational Culture; Organizational Commitment; Employee Performance.